Mega Events and innovative mobility system: the Expo transport lessons - Papa, Enrica (TeMA - Journal of Land Use, Mobility and Environment, 2008)
Mega events have been defined as a form of “speeding up” for urban system transformation (Boeri 2008) and for the implementation of ground-breaking policies in host cities. This term is even more appropriate if is referred to the construction of pioneering mobility systems. Big events and in particular Expo constitute opportunities for the building up of innovative solution for urban mobility, the diffusion and the testing of new technology and prototypes. This article, starting from a review of international study cases, shows how the construction of mobility systems for International Expo is an occasion of testing and constructing innovative transport infrastructures oriented to the mobility of the future (Richards 2001). The article illustrate this phenomena trough the study of the evolution during the last fifty years of transport planning and design in ten different Expo, describing the main mobility challenges and the proposal for the mobility of the future. The study defines three different cluster of Expo: the first group of Expo is called the “progress and speed” Expo and reflect the general approach of mobility planning in the ‘60 and ‘70 Expo; the second cluster include the ‘80 and ‘90 Expo, that are defined as the “automobile dependence” Expo, in which the innovation for urban public transport was limited by the huge diffusion of cars in these decades. The last cluster are the new millennium Expo: the “zero emission” Expo, where the research for green mobility is the main transport challenge.